Cholecystokinin in the gut: how many function? Observations in a Teleost : White Sea Bream (Diplodus sargus) - Valeria Micale; D'ASCOLA, ANGELA; GUERRERA, Maria Cristina; CAMPO, Salvatore Giuseppe; LEVANTI, Maria; GERMANA', Antonino; MUGLIA, Ugo (--, 2013)
As known the function of gut peptide hormone cholecystokinin (CCK) is involved in the regulation of food intake and satiation. Immunohistochemical studies conducted in larval and adult teleosts fish have demonstrated high density of CCK-immunoreactive cells (CCK-ir) in the anterior midgut and pyloric caeca where the ingested food is retained longest and can be best attacked by digestive enzymes particularly in species with a rotated gut. In the adult CCK has been demonstrated, in the hindgut, by means of RT-PCR or immunohistochemistry in four species (rainbow trout, Japanese yellowtail, turbot and atlantic salmon) while it has been excluded in five (gilthead sea bream, Japanese flounder, Korean aucha perch, brown trout and red drum). It has been hypothesized that hindgut CCK-ir cells might participate in the feedback control of digestive processes, by receiving chemical signals from uncompletely digested food. However, the finding of different expression patterns of multiple intestinal CCK isoforms in the same individual, as in both rainbow trout and Atlantic salmon, is also suggestive of different roles exerted by midgut and hindgut CCK. For above reasons the regional distribution of intestinal CCK in Diplodus sargus as well as the possible involvement of hindgut CCK in digestive processes were investigated. Full-lengths mRNAs encoding two CCK isoforms (CCK-1 and CCK-2) were sequenced and phylogenetically analyzed. CCK gene and protein expression levels in the different gut segments were measured 3 h and 72 h after feeding, by quantitative real-time RT-PCR and Western blot, respectively. Moreover, endocrine CCK cells were immunoistochemically detected. The results demonstrated two CCK isoforms in the hindgut of D.sargus, one of which (CCK-2) may be involved in the feedback control of uncompleted digestive processes while a functional role alternative to regulation of digestive processes may be inferred for D.sargus CCK-1, since its expression was unaffected by feeding or fasting.